Analysis of Advertising Language Use and Media Utilization on YouTube in Promoting Universitas Nurtanio Bandung - Merlina, Tina (Linguistik : Jurnal Bahasa dan Sastra, 2024)
This research aims to determine the use of language and language functions in Universitas Nurtanio Bandung promotional content on YouTube. In addition, this research also aims to determine the use of YouTube media in promoting Universitas Nurtanio Bandung. Researchers took data from several videos on the YouTube channel of Universitas Nurtanio Bandung. This research is a qualitative research. To analyze language use and language functions, researchers used the theory of Searle (1969). The results of the research show that the promotional advertising content of Universitas Nurtanio Bandung on YouTube uses illocutionary acts in the form of assertive and directive speech acts. The function of this speech is convival and colaborative. Universitas Nurtanio Bandung actively uses YouTube to promote the university. It is hoped that this research can provide input for UNNUR to use advertising language more in the form of offers and recommendations. Content promotion on other social media such as Tiktok or Instagram can be used for further research.Keywords: Language, Speech Act, YouTube